2015
DOI: 10.2214/ajr.14.13492
|View full text |Cite
|
Sign up to set email alerts
|

ALARA: Impact of Practice Quality Improvement Initiative on Dose Reduction in Pediatric Voiding Cystourethrogram

Abstract: This project changed practice by substituting last-image capture for digital-spot images without affecting vesicoureteral reflux grading while reducing radiation exposure. Monitoring DAP is a better assessment of radiation exposure than is fluoroscopy time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Studies have demonstrated significant variability among institutions lacking standardized VCUG protocols, as well as inconsistent reporting practices [23,24]. In addition to potential child and parental distress, VCUGs also expose patients to ionizing radiation, albeit at low doses [25,26]. It is important to collaborate with the radiologist to optimize the quality and quantity of data obtained from a single VCUG.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated significant variability among institutions lacking standardized VCUG protocols, as well as inconsistent reporting practices [23,24]. In addition to potential child and parental distress, VCUGs also expose patients to ionizing radiation, albeit at low doses [25,26]. It is important to collaborate with the radiologist to optimize the quality and quantity of data obtained from a single VCUG.…”
Section: Discussionmentioning
confidence: 99%
“…However, this technique might miss low-grade VUR, which is usually insignificant. 120 Fluoroscopy time during VCUG has recently tended to decrease. 121 Ngo et al evaluated data from 987 VCUG examinations and concluded that increasing fluoroscopy time during VCUG does not necessarily increase diagnostic accuracy of VUR detection.…”
Section: Alara: Radiation Exposure Reduction Methodsmentioning
confidence: 99%
“…In accordance with the ALARA principle (“as low as reasonably achievable”), last‐image capture for digital‐spot images can reduce radiation exposure without compromising diagnostic accuracy. However, this technique might miss low‐grade VUR, which is usually insignificant . Fluoroscopy time during VCUG has recently tended to decrease .…”
Section: Radiologists’ Efforts To Reduce Drawbacks Of Vcugmentioning
confidence: 99%
“…1,2 The ongoing discussion concerning radiation protection in terms of the as low as reasonably achievable principle demands reduction of the radiation dose down to a level at which image quality is still diagnostically sufficient. 4 However, the clinically applied dose often relies on manufacturer's recommendations and is not necessarily the lowest possible dose that can be achieved in clinical routine. One important and well-examined role in dose-reduction strategies is using mathematic models such as iterative reconstruction (IR) to reduce image noise and thus allow a lower radiation dose.…”
mentioning
confidence: 99%